1985
DOI: 10.1111/j.1439-0388.1985.tb00705.x
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotrope Wirkungen von β‐Lactoglobulin‐ und Casein‐Genotypen auf Milchinhaltsstoffe des bayerischen Fleckviehs und Braunviehs1

Abstract: Zusammenfassung An zwei umfangreichen Stichproben der bayerischen Fleckvieh‐ und Braunviehpopulation mit jeweils etwa 2000 Tieren wurden bei den Merkmalen Milchserumeiweißgehalt, Caseingehalt, Gesamteiweißgehalt und Fettgehalt pleiotrope Wirkungen von β‐Lactoglobulin‐ und Casein‐Genotypen geschätzt. Alle Genotypen zeigten bei allen Eigenschaften und bei beiden Rassen Einflüsse, wobei zwischen den Wirkungen der Fleckvieh‐ und Braunviehpopulation eine gute Übereinstimmung deutlich wird. Die deutlichsten Effekte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 5 publications
(4 reference statements)
3
17
1
1
Order By: Relevance
“…The frequencies of κ-Cn A and B were similar to that of Graml et al (1984) and Ortner et al (1995), while the frequency of κ-Cn A was higher than that of Putz et al (1991) and lower than that of Erhardt (1993) and Falaki et al (1997). The frequencies of β-Lg A and B were equal, in agreement with the findings of Graml et al (1984) and Putz et al (1991). The frequency of β-Lg B was higher than that reported by Erhardt (1993) and Falaki et al (1997) and lower than the result of Ortner et al (1995).…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…The frequencies of κ-Cn A and B were similar to that of Graml et al (1984) and Ortner et al (1995), while the frequency of κ-Cn A was higher than that of Putz et al (1991) and lower than that of Erhardt (1993) and Falaki et al (1997). The frequencies of β-Lg A and B were equal, in agreement with the findings of Graml et al (1984) and Putz et al (1991). The frequency of β-Lg B was higher than that reported by Erhardt (1993) and Falaki et al (1997) and lower than the result of Ortner et al (1995).…”
Section: Resultssupporting
confidence: 81%
“…The frequencies of β-Lg A and B were nearly similar to the findings of Panicke et al (1996) and McLean et al (1984), but were lower than that reported by Erhardt (1993) and higher than the results of Bobe et al (1999). For Simmentaler cows the frequency of α S1 -Cn B was higher and that of α S1 -Cn C lower than the results of Graml et al (1984), Putz et al (1991), Erhardt (1993), Ortner et al (1995) and Falaki et al (1997). The frequencies of β-Cn A 1 and B were higher and that of allele A 2 lower than the frequencies reported by other researchers (Putz et al, 1991;Erhardt, 1993;Ortner et al, 1995).…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…These results do not agree with those obtained by Haenlein [58] and Graml [59] in relation to the stained brown bavárico and Guernsey, who claim that cows carrying the AB genotype reach a higher milk production compared to those with the homozygous genotype AA. On the contrary, [6,60,61] they reported the highly significant effect of genotype BB on this feature in the Holstein breed.…”
Section: Allelic Variants Of κ-Cscontrasting
confidence: 56%